Criminal Liability of Perpetrators of Unauthorized Management of Medical B3 Waste Without License: (Study of Decision Number 115/Pid.B/LH/2019/PN Slt and Decision Number 1/PID.B/LH/2020/PT Smg) - Anaria Br Ginting; Alvi Syahrin; Edi Yunara; Jelly Leviza (Locus Journal of Academic Literature Review, 2023)
Criminal responsibility leads to the perpetrator with the intention of determining whether the defendant or suspect can be held accountable for a criminal offense that occurs. Solid Medical Hazardous Waste is goods or materials left over from activities that are not reused which have the potential to be contaminated by infectious substances. The Indonesian Ombudsman in 2021 noted that there were at least 138 million tons of medical waste that were not properly managed, so it is necessary to deal with the management of medical B3 waste in Indonesia. This research uses normative juridical legal research because it wants to examine laws and regulations and judges' decisions relating to the management of B3 waste without a license. The approach in this research uses a case approach by examining the case in Decision Number 115/Pid.B/LH/2019/PN Slt and Decision Number 1/Pid.B/LH/2020/PT Smg which have permanent legal force. The conclusion in the study shows that in Decision Number 115/Pid.B/LH/2019/PN Slt and Decision Number 1/Pid.B/LH/2020/PT Smg is that the criminal liability of the perpetrators of medical B3 waste management at Salatiga Regional Hospital is not correct regarding the application of the law, this is because the judge in deciding this case did not pay attention to changes in the rules related to the article charged had been deleted by the Job Creation Law before the judge made a decision. The defendant should have been acquitted of the criminal charges.